Penerapan Metode Choice Based Conjoint - Hidaya Annur; Desi Yuniarti; Ika Purnamasari (EKSPONENSIAL, 2019)
Lecturer is an important factor in the process of teaching and learning process in universities. This study was conducted with the aim to know the characteristics of students of Statistics Program Department of Mathematics at FMIPA Mulawarman University on the characteristics of the expected lecturers. One method that can be used to know the options is the conjoint-based optional method. Choice Based Conjoint (CBC) is a conjoint analysis that measures preferences based on conceptual choices and is used to determine the concept of attributes of lecturer characteristics expected by students. Attributes used in this study are the background of lecturers, lecturer characters, learning methods and interaction in the class. The data analysis technique used in the conjoint-based optional method is the conditional logit model. The result of CBC analysis shows that the attribute that is considered most important by the respondents based on attribute importance value is classroom interaction with percentage of 48,41% and seen from the value of the utility of interaction in the class with a positive value is the interaction in the active class with a value of 1.331. The characteristics of lecturers that are expected to be possessed by lecturers are casual lecturer character, last doctoral education, creative teaching methods and active classroom interaction.